The role of central, regional and local administrations in the application of the Kyoto protocol in the forestry sector in Italy - Pompei E; Federici S; Vitullo M; Tedeschi V; Lumicisi A (Forest@, 2007)
According to art. 3.3 and 3.4 of the Kyoto Protocol and subsequent UNFCCC COP's and national decisions, Italy shall report the net changes in GHG emissions by sources and removals by sinks resulting from afforestation, reforestation and deforestation (art. 3.3) and forest management (art. 3.4) activities. To assess art. 3.3 activities, Italy will define methods to estimate land use changes occurring after 31 December 1989. The paper considers the key-role that central administration shall have, as well as the role of regional and local administrations in order to solve some specific topics regarding data collection and management issues.